Tunable spin selective transport and quantum phase transition in parallel double dot system. (February 2016) - Xiong, Yong-Chen; Wang, Wei-Zhong; Luo, Shi-Jun; Yang, Jun-Tao
Abstract: We study theoretically the spin selective transport and the quantum phase transition (QPT) in a double dot device by means of the numerical renormalization group technique. When the gate voltage ε is in the Kondo regime and the interdot hopping t is large enough, a first order QPT between local spin singlet and S z =1 of the triplet is observed as the magnetic field B increases. Beyond the Kondo regime, the QPTs depend closely on ε and t, and perfect spin filter is found, where the effect of spin filtering could easily be manipulated by tuning external parameters. We show that the interplay between the Zeeman effect and the antiferromagnetic interdot hopping, and occupancy switching are responsible for the QPT and the spin selective transport. Highlights: Spin filter which does not rely on spin-polarized leads or the Rashba spin-orbit interaction is realized. The effect of spin filtering could easily be manipulated by external parameters. A wealthy of quantum phase transitions are shown.